(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
This study investigates clause structure and grammatical relations in Old Javanese texts Uttara Śabda Amrta and Parttha Adnyana Sura from the Merapi–Merbabu Bali locus. Using a qualitative-descriptive method and Lexical-Functional Grammar analysis, the study identifies linear structures, f-structure relations, and the interaction between syntactic functions such as Subject, Predicate, Object, and Complement. Findings reveal declarative, interrogative, and imperative clauses with specific patterns and relational hierarchies, showing how grammatical constructions convey meaning in textual discourse. This research contributes to a deeper understanding of Old Javanese syntax and the systematic use of grammatical relations in classical manuscripts